Causal inference in space weather by an information theory approach. (May 2020) - Stumpo, M; Consolini, G; Alberti, T
Abstract: The variability of the interplanetary medium and solar wind conditions strongly affects the near-Earth environment causing several phenomena, such as the magnetic storms and substorms. Here, we present some preliminary results on the causal inference in the solar wind-magnetosphere-ionosphere coupling by means of information theory which could be helpful for Space Weather modeling.